2013
DOI: 10.1227/neu.0b013e31828bae28
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Bilateral Vestibular Schwannomas in Neurofibromatosis Type 2 Patients

Abstract: : AAO-HNS, American Academy of Otololaryngologists and Head and Neck Surgery classificationMTD, mean tumor diameterNF2, neurofibromatosis type 2PTA, pure-tone averageSDS, speech discrimination scoreVS, vestibular schwannomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
1
30
1
2
Order By: Relevance
“…For trials focused on prevention of hearing decline, we found that patients in our cohort with medium/large tumors (≥ 1 ml) at study enrollment had a shorter median time to hearing decline (38 months) than small tumors (median not reached), and thus represent a more feasible group to study in clinical trials. While rate of tumor growth is not correlated to hearing preservation, 11 our results showed a correlation between larger baseline tumor size and subsequent hearing loss. For this reason, we propose that NF2 patients with VS ≥ 1 ml be stratified as "high risk" for subsequent hearing decline, and that consideration be given to making these patients eligible for trials without the need for documented tumor progression at study enrollment.…”
Section: Trial Design: Time To Hearing Decline or Tumor Progression Acontrasting
confidence: 65%
See 1 more Smart Citation
“…For trials focused on prevention of hearing decline, we found that patients in our cohort with medium/large tumors (≥ 1 ml) at study enrollment had a shorter median time to hearing decline (38 months) than small tumors (median not reached), and thus represent a more feasible group to study in clinical trials. While rate of tumor growth is not correlated to hearing preservation, 11 our results showed a correlation between larger baseline tumor size and subsequent hearing loss. For this reason, we propose that NF2 patients with VS ≥ 1 ml be stratified as "high risk" for subsequent hearing decline, and that consideration be given to making these patients eligible for trials without the need for documented tumor progression at study enrollment.…”
Section: Trial Design: Time To Hearing Decline or Tumor Progression Acontrasting
confidence: 65%
“…Several single-institution clinical series have been reported from NF2 centers, but these have typically been small and retrospective. [7][8][9][10][11] In addition, many of these studies have reported results primarily as the average growth rates or hearing decline among all subjects. This measure is less useful in designing clinical trials for drug treatment of NF2-related VS. For this purpose, an understanding of individual times to failure for measures such as tumor growth or hearing decline in untreated patients is required.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In large NF2-associated VS natural history studies, the average growth in greatest diameter per year was reported to be between 1.3 and 1.8 mm, corresponding to a 10%-14% increase from the baseline averages of 12.4 and 13.0 mm. 27,28 Another study evaluated the feasibility of volumetric assessment of VS and demonstrated increased sensitivity in detecting disease progression and reduced intrarater measurement variability compared to linear measurements.…”
mentioning
confidence: 99%
“…These suggest that hearing deteriorates by approximately 3 dB/year. Studies investigating NF2 patients are fewer in number but suggest the rate of hearing loss is similar with an annual change in pure tone average of around 4 dB and an annual change in speech discrimination scores of around 2 % [6,9,[22][23][24]. Only a recent study by Peyre et al [23] present preservation of hearing serviceability data and they state a figure of 74 % over a 72-month period on average.…”
Section: Discussionmentioning
confidence: 99%